2008
DOI: 10.1182/blood-2008-05-159301
|View full text |Cite
|
Sign up to set email alerts
|

Differential Th17 CD4 T-cell depletion in pathogenic and nonpathogenic lentiviral infections

Abstract: Acute HIV infection is characterized by massive loss of CD4 T cells from the gastrointestinal (GI) tract. Th17 cells are critical in the defense against microbes, particularly at mucosal surfaces. Here we analyzed Th17 cells in the blood, GI tract, and broncheoalveolar lavage of HIV-infected and uninfected humans, and SIV-infected and uninfected sooty mangabeys. We found that (1) human Th17 cells are specific for extracellular bacterial and fungal antigens, but not common viral antigens; (2) Th17 cells are inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
659
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 570 publications
(704 citation statements)
references
References 52 publications
38
659
3
4
Order By: Relevance
“…Preferential depletion of Th17 CD4 T cells has been found in HIV-infected individuals as well as in pathogenic SIV-infected monkeys (24). Our data showed that a significant fraction of Ad5-specific CD4 T cells, but not CMV-specific CD4 T cells, produce IL-17.…”
Section: Discussionsupporting
confidence: 59%
“…Preferential depletion of Th17 CD4 T cells has been found in HIV-infected individuals as well as in pathogenic SIV-infected monkeys (24). Our data showed that a significant fraction of Ad5-specific CD4 T cells, but not CMV-specific CD4 T cells, produce IL-17.…”
Section: Discussionsupporting
confidence: 59%
“…First and foremost, it is possible that a different "quality" of CD4 ϩ T-cell depletion in natural versus nonnatural SIV hosts at the intestinal mucosal level plays a major role. Indeed, both SIV-infected RM and HIV-infected persons experience a significant and preferential reduction of the IL-17-producing CD4 ϩ (Th17) and CD8 ϩ (Tc17) T-cell subsets throughout the gastrointestinal tract (81)(82)(83)(84). Similarly, the depletion of IL-17-producing innate lymphocytes in the GI tracts of SIV-infected Asian macaques has been demonstrated (85,86).…”
Section: Pathogenesis Of Hiv/siv-associated Microbial Translocationmentioning
confidence: 99%
“…The high susceptibility of Th17 cells to HIV, due to the large tropism of the virus in response to CCR5 chemokine receptor, is reflected in the depletion of this profile, in both the PBMC and gut-associated lymphoid tissue (GALT) of seropositive patients 88,89 . However, Th17 cells were found preserved in LTNP individuals 90 .…”
Section: Th17: Promotion Of Homeostasis or Inflammatory Status?mentioning
confidence: 99%